INTEGRATED MARKETING COMMUNICATION STRATEGY OF PT. JOGJAKITA MULTI ANDALAN IN INCREASING BRAND AWARENESS AS A LOCAL ON DEMAND SERVICES BUSINESS IN 2020-2022 - Yasmimmuntaz, Rajakansa; Rahman, Taufiqur (International Conference on Humanity Education and Society (ICHES), 2024)
This research aims to determine and describe the implementation of the concept ofpromotion mix elements in the integrated marketing communications strategy of PT.JogjaKita Multi Andalan in increasing brand awareness as a local on-demand servicein 2020-2022. This research uses a qualitative descriptive approach with datacollection methods through interviews, documentation and literature study. Theinformants in this research were JogjaKita employees and JogjaKita users. Theresearch results show that JogjaKita is an application from a startup company thatoperates in the local ride-hailing sector by carrying out promotions by integratingseven promotional methods, namely: Advertising (billboards, vouchers, brochures,leaflets); direct marketing (SEO, Google, SEM, official site). Interactive marketing(Facebook, YouTube, Instagram, TikTok). Public Relations and Publicity (cooperatingwith SMEs assisted by SiBakul Jogja from Diskop DIY, holding MSME entrepreneurshiptraining, public relations, social media publications and social assistance). Events andexperiences (holding a gimmick event on a certain day, visiting a school). Word ofmouth marketing (campaigns, recommendations, testimonials, e-commerce reviews,person-to-person stories). Sales promotions (giving discounts or bonus points throughthe application). JogjaKita's brand awareness is currently at the brand recognitionlevel.